2016
DOI: 10.1002/aenm.201502423
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Optimizing Electrical and Thermal Transport Properties of BiCuSeO via a Dual‐Doping Approach

Abstract: The layered oxyselenide BiCuSeO system is known as one of the high‐performance thermoelectric materials with intrinsically low thermal conductivity. By employing atomic, nano‐ to mesoscale structural optimizations, low thermal conductivity coupled with enhanced electrical transport properties can be readily achieved. Upon partial substitution of Bi3+ by Ca2+ and Pb2+, the thermal conductivity can be reduced to as low as 0.5 W m−1 K−1 at 873 K through dual‐atomic point‐defect scattering, while a high power fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(147 citation statements)
references
References 31 publications
3
142
1
1
Order By: Relevance
“…5,6 On the other hand, structural manipulations have been adopted to suppress the thermal conductivity, such as introducing nanoscale structures to reduce the phonon mean free path, point defect scattering through alloying with other elements, and lone pair electron to develop soft phonon modes. [7][8][9][10][11] As the thermoelectric transport characteristics depend on interrelated material properties, 4 simultaneous enhancement of the power factor and decrease of the thermal conductivity are challenging. 15 Besides, CZTSe nanocrystals with relatively low thermal conductivity showed that the maximum zT is 0.44 at 723K for CZTSe 16 and 0.7 at 723K for Cu 2.1 Zn 0.9 SnSe 4 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 On the other hand, structural manipulations have been adopted to suppress the thermal conductivity, such as introducing nanoscale structures to reduce the phonon mean free path, point defect scattering through alloying with other elements, and lone pair electron to develop soft phonon modes. [7][8][9][10][11] As the thermoelectric transport characteristics depend on interrelated material properties, 4 simultaneous enhancement of the power factor and decrease of the thermal conductivity are challenging. 15 Besides, CZTSe nanocrystals with relatively low thermal conductivity showed that the maximum zT is 0.44 at 723K for CZTSe 16 and 0.7 at 723K for Cu 2.1 Zn 0.9 SnSe 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The zT of BiCuSeO has been increased to~1.5 through various approaches (see Fig. 17 b-f) including element doping (Mg, Sr, Ca, Ba, Pb at Bi site, Cu vacancies) [51,53,59,165,166], alloying (S, Te) [167], modulation doping [57] and texture treatment [56]. The findings and design methodology of this material are of valuable significance to investigation on similar layered compounds such as SnSe.…”
Section: Other High-performance Cu-based Chalcogenidesmentioning
confidence: 99%
“…3a, Cu 2 Se possesses two sublattices: the rigid FCC framework of Se atoms and the disordered and flowing sublattice of Cu. At high temperatures, Cu ions migrate from one site (interstitial one formed by Se) to another, exhibiting a flowing character that is Figure 1 Timeline of zT for selected Cu-based superionic conductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (red), tetragonal [28][29][30][31][32][33][34][35][36][37] (blue) and distorted [38][39][40][41][42][43][44][45][46][47][48][49] (green) diamond-like materials and BiCuSeO oxyselenides (purple) [50][51][52][53][54][55][56][57][58][59]…”
Section: Decoupled Transport Properties By Two Independent Sublatticesmentioning
confidence: 99%
“…Recently, Pb/Ca co-doping has been reported as an efficient way to enhance the TE properties of BiCuSeO [17,58]. Under Pb/Ca co-doping, the PF of BiCuSeO has reached 10 × 10 −4 W/mK 2 at room temperature [58].…”
Section: Bicuseomentioning
confidence: 99%